Efficient Degradation of Zearalenone by Dye-Decolorizing Peroxidase from Streptomyces thermocarboxydus Combining Catalytic Properties of Manganese Peroxidase and Laccase - Xing Qin; Yanzhe Xin; Xiaoyun Su; Xiaolu Wang; Yaru Wang; Jie Zhang; Tao Tu; Bin Yao; Huiying Luo; Huoqing Huang (Toxins, 2021)
Ligninolytic enzymes, including laccase, manganese peroxidase, and dye-decolorizing peroxidase (DyP), have attracted much attention in the degradation of mycotoxins. Among these enzymes, the possible degradation pathway of mycotoxins catalyzed by DyP is not yet clear. Herein, a DyP-encoding gene, StDyP, from Streptomyces thermocarboxydus 41291 was identified, cloned, and expressed in Escherichia coli BL21/pG-Tf2. The recombinant StDyP was capable of catalyzing the oxidation of the peroxidase substrate 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), phenolic lignin compounds 2,6-dimethylphenol, and guaiacol, non-phenolic lignin compound veratryl alcohol, Mn2+, as well as anthraquinone dye reactive blue 19. Moreover, StDyP was able to slightly degrade zearalenone (ZEN). Most importantly, we found that StDyP combined the catalytic properties of manganese peroxidase and laccase, and could significantly accelerate the enzymatic degradation of ZEN in the presence of their corresponding substrates Mn2+ and 1-hydroxybenzotriazole. Furthermore, the biological toxicities of the main degradation products 15-OH-ZEN and 13-OH-ZEN-quinone might be remarkably removed. These findings suggested that DyP might be a promising candidate for the efficient degradation of mycotoxins in food and feed.